2019
DOI: 10.1093/eurheartj/ehz852
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac sympathetic co-transmitter neuropeptide Y is pro-arrhythmic following ST-elevation myocardial infarction despite beta-blockade

Abstract: Aims ST-elevation myocardial infarction is associated with high levels of cardiac sympathetic drive and release of the co-transmitter neuropeptide Y (NPY). We hypothesized that despite beta-blockade, NPY promotes arrhythmogenesis via ventricular myocyte receptors. Methods and results In 78 patients treated with primary percutaneous coronary intervention, sustained ventricular tachycardia (VT) or fibrillation (VF) occurred in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…Activation of sympathetic system predisposes to ischemia-induced VF [ 22 , 23 ] that can be based on several mechanisms mediated by catecholamine-related [ 24 ] as well as neuropeptide Y-related [ 25 ] signaling. The proarrhythmic effects of sympathetic activation include facilitation of ectopic activity by abnormal automaticity and afterdepolarizations [ 26 , 27 , 28 , 29 ], increase in DOR [ 30 ] and inhomogeneous conduction [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of sympathetic system predisposes to ischemia-induced VF [ 22 , 23 ] that can be based on several mechanisms mediated by catecholamine-related [ 24 ] as well as neuropeptide Y-related [ 25 ] signaling. The proarrhythmic effects of sympathetic activation include facilitation of ectopic activity by abnormal automaticity and afterdepolarizations [ 26 , 27 , 28 , 29 ], increase in DOR [ 30 ] and inhomogeneous conduction [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, we speculate that in post-MI subjects with high mortality risk, increased amplitude of PRD oscillations might reflect a higher degree of synchronization among cardiac presympathetic and preganglionic neurons which would allow the recruitment of previously silent postganglionic fibers that innervate specific targets within the heart, such as the myocardium. This would result in the release of copious amounts of norepinephrine from the sympathetic terminals and perhaps the release of arrhythmogenic cotransmitters such as Neuropeptide Y (Kalla et al, 2019) which may ultimately precipitate profound periodic changes in ventricular repolarization.…”
Section: Resultsmentioning
confidence: 99%
“…Optical mapping experiments in rats showed that NPY steepens the action potential duration restitution curve [86]. Very recently, in Langendorff-perfused rat hearts with intact innervation, Y1 receptor activation was associated with a significant reduction in ventricular fibrillation threshold despite metoprolol that was accompanied by increased amplitude and decreased duration of intracellular calcium transients [93]. Finally, NPY is also a potent vasoconstrictor [94].…”
Section: Cardiac Sympathetic Efferent Neuronsmentioning
confidence: 99%